JENIS ASAM LEMAK MINYAK TEMPE BUSUK - Rachmawati, M. H.; Soetjipto, H.; A. Ign. Kristijanto, A. Ign (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019DO - 10.24843/JCHEM.2019.v13.i01.p13, 2019)
Overripe tempe is a food product that used by peoples in Indonesia as a food seasoning. So far, overripe tempe received less attention than fresh tempe and research of overripe tempe is rarely done. The objective of the study is to identify the fatty acid compounds of the  fifth day fermentation overripe tempe oil before and after purification . The overripe tempe oil of fifth day fermentation was extracted with soxhletation method using n – hexane solvent, then it was purified. The various fatty acids  of overripe tempe oil were analyzed by GC – MS. The purification process was done by using H 3 PO 4 0,2% and NaOH 0,1N. The result of the study showed that before purification the oil  was composed of eight compounds  are palmitic acid (13,33%),  linoleic acid (77,57%), stearic acid (6,15%), and the five chemical components, Dasycarpidan – 1 - methanol, acetate ,  oleic acid , 9 - Octadecenamide ,Cholestane - 3, 7, 12, 25 - tetrol, tetraacetate, (3?, 5?, 7?, 12?) and   6, 7 – Epoxypregn – 4 – ene -9, 11, 18- triol - 3, 20 - dione, 11, 18 – diacetate have percentage of areas less than 3%. After purification the oil  was composed of palmitic acid (12,38% ), linoleic acid (80,35 %), stearic acid (5,84%), and 17 – Octadecynoic acid (1,42 %) .